Archi Responds to Pettinato (The Biblical archaeology review, 1980)
The original Italian article from which the foregoing article by Professor Pettinato was adapted has not gone unanswered. Professor Archi has responded to Professor Pettinato in the Italian journal Studi Eblaiti in an article entitled, "Ancora Sul-Ebla e la Biblia" ("Again on Ebla and the Bible"). With this summary of Professor Archi’s recent response […]